A multiple-extension adaptive Huffman code - Agustin, Luisito L.
This thesis consists of the design, implementation, and evaluation of a lossless data compression code that uses adaptive Huffman techniques for encoding multiple extensions of a source alphabet. The proposed code uses dual encoding trees as in [Lu..] along with modifications to the adaptive Huffman code [Gallager] that allow the algorithm to handle multiple extensions of the source as is done in dictionary-based compressors. The compression ratios achieved using a software implementation of the proposed code is evaluated against compression ratios achieved by other data compression schemes. Results show that the proposed code achieves better compression ratios Huffman-type codes and LZW. However, the higher compression ratios do not exceed those achieved by high orders of arithmetic coding and popular data compression utilities in use.